2002
DOI: 10.1124/jpet.102.037945
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/Orphanin FQ Modulation of Ionic Conductances in Rat Basal Forebrain Neurons

Abstract: Nociceptin/orphanin FQ (N/OFQ) is an endogenous opioid-like heptadecapeptide that plays an important role in a variety of physiological functions. N/OFQ and its receptor opioid receptor-like orphan receptor-1 are abundant in the diagonal band of Broca (DBB), a basal forebrain nucleus where the loss of cholinergic neurons is linked to memory and spatial learning deficits. In the whole animal, central injections of N/OFQ have been shown to disrupt spatial learning. In this study, we investigated the basis for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
(50 reference statements)
0
9
0
Order By: Relevance
“… Bigoni et al ., 2000 ; Ozaki et al ., 2000a ; 2000b ; Ichikawa et al ., 2001 ) or those employing CompB for verifying that actions of N/OFQ are mediated through the NOP receptor (e.g. Chin et al ., 2002 ; Mela et al ., 2004 ). In vivo studies employing CompB are fewer, although an appreciable number have recently accumulated.…”
Section: Discussionmentioning
confidence: 99%
“… Bigoni et al ., 2000 ; Ozaki et al ., 2000a ; 2000b ; Ichikawa et al ., 2001 ) or those employing CompB for verifying that actions of N/OFQ are mediated through the NOP receptor (e.g. Chin et al ., 2002 ; Mela et al ., 2004 ). In vivo studies employing CompB are fewer, although an appreciable number have recently accumulated.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for preparation of tissue was reviewed and approved by the University of Alberta Health Sciences Laboratory Animal Services (Protocol number 154/04/05). Details of the procedure for acute dissociation of neurons from the DBB have been previously described (Chin et al, 2002). Briefly, brains were quickly removed from decapitated male Sprague Dawley rats (21-25 days postnatal) and placed in cold artificial cerebrospinal fluid (ACSF) that contained (in mM) 140 NaCl, 2.5 KCl, 1.4 CaCl 2 , 5 MgCl 2 , 10 HEPES, and 33 Dglucose (pH 7.4).…”
Section: Dissociation Proceduresmentioning
confidence: 99%
“…Dissociated cells were then plated on poly-L-lysine (0.005% w/ v)-coated cover slips and viewed under an inverted microscope (Zeiss Axiovert 35). Neurons were identified based upon previously established visual criteria (Chin et al, 2002). Basal forebrain neurons could be differentiated from glia based upon the presence of truncated dendrites at the conspicuously larger neurons.…”
Section: Dissociation Proceduresmentioning
confidence: 99%
“…In addition, N/OFQ was found to inhibit voltage-gated calcium currents. Although we cannot rule out an effect on other ionic currents known to be modulated by N/OFQ such as BK and delayed rectifier currents (Chin et al 2002;Qu et al 2007), we conclude that the majority of the observed inhibition of MCH neurons results from modulation of GIRK and calcium channel activity.…”
Section: Discussionmentioning
confidence: 93%